Movimento negro educador: contribuições para uma prática pedagógica antirracista - Silva Souza, Eula Paula da (Universidade Federal de São Carlos, 2025)
This work aims to reflect on the contributions of the Black Educator Movement (Movimento Negro Educador) to pedagogical practices and the school curriculum, especially in the context of basic education. It is based on the understanding that school curricula, historically marked by a Eurocentric perspective, tend to silence or marginalize the knowledge and experiences of the Black population. The research, qualitative in nature and with a theoretical approach, is grounded in the works of authors such as Nilma Lino Gomes (2017), Kabengele Munanga (2004), Eliane Cavalleiro (2001), Petronilha Beatriz Gonçalves e Silva (2003), and Beatriz Nascimento (1985), who discuss education on ethnic-racial relations, Black epistemologies, and quilombismo as a form of resistance and knowledge production. The legal framework adopted is Law 10.639/03, which amended the Brazilian Law of Guidelines and Bases (LDB) to include the teaching of Afro-Brazilian and African history and culture in the school curriculum. The effectiveness of this law depends on anti-racist pedagogical practices and the valorization of Black voices within educational spaces. The Black Educator Movement, a concept primarily developed by Nilma Lino Gomes, is understood as a set of actions, individuals, memories, and struggles that, throughout history, have challenged the Brazilian educational system and formulated strategies to confront structural racism.By recognizing this movement as a producer of pedagogical knowledge, this work seeks to highlight how its practices influence teacher education, curriculum organization, and the construction of a school that values diversity and combats racial inequalities. This study shows that the Black Educator Movement is a political, pedagogical, and epistemic force capable of transforming school practices and inspiring the development of an anti-racist, plural education committed to social justice. In this sense, the study contributes to strengthening the struggle for a school that not only includes Afro-Brazilian content, but also reconfigures itself based on Black epistemologies and attentive listening to those historically silenced by the hegemonic curriculum
Black educator movement: contributions to an anti-racist pedagogical practice
Keywords: Movimento negro educador; Práticas pedagógicas; Currículo.; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM